Is there scientific evidence that sauna bathing enhances the health effects of physical activity? - Review - Elias , Jagoda; Biesiada, Wiktor; Zubiak, Marlena; Błaszków, Krzysztof; Szydłowska, Sara; Kaźmierczak, Dominika (Quality in Sport, 2025)
Introduction Sauna bathing and sport are well-known methods of improving a person’s overall health. These activities not only have a positive impact on mental wellbeing, but also have a real effect on improving certain physical parameters such as, for example, blood pressure. Aim of the review A summary of the information gathered to date on the health effects of sauna bathing and undertaking physical activity. Results The results of the studies cited in this article are consistent: sauna enhances the positive effects of physical activity on cardiovascular function among people with at least one major cardiovascular risk factor and who are not professional athletes. Conclusions Although sauna seems to increase the health effects of physical activity one should be aware of the contraindications to its use. Additionally, it is worth conducting more large scale randomized trials to verify this information.